Tub Tim Siam Rice: Applications in Cosmeceutical Products - Kaewsrichan, Jasadee -; Wangpradit, Nuntika (Science Essence Journal, 2019)
บทคัดย่อ ข้าวทับทิมสยามเป็นพันธุ์ข้าวพื้นเมืองของประเทศไทย เมล็ดมีสีแดง นำข้าวที่กะเทาะเปลือกออก แล้วมาบดให้ละเอียด สกัดผงข้าวด้วยเอทานอล จากนั้นวิเคราะห์หาชนิดของสารประกอบในสารสกัดข้าวด้วยเทคนิค GC-MS และ HPLC, ปริมาณสารประกอบฟีนอลิกทั้งหมดด้วยน้ำยา Folin-Ciocalteu, ฤทธิ์ต้านออกซิเดชันด้วยเทคนิค Diphenyl-picryhydrazyl (DPPH) radical scavenging activity assay และ Ferric (Fe3+) reducing antioxidant power (FRAP) assay และคุณสมบัติช่วยสมานแผลด้วยวิธี Scratch Test พบว่าสารสกัดข้าวฯมีสารแอนโธไซยานิน กรดไขมันสายโซ่ยาว และเอสเทอร์ของกรดไขมันสายโซ่ยาวเป็นองค์ประกอบ ปริมาณสารประกอบฟีนอลิกทั้งหมดเท่ากับ 1.5 mg gallic acid equivalent/g rice powder ค่า DPPH radical scavenging activity เท่ากับ 8 mg Trolox equivalent/g rice powder และค่า FRAP activity เท่ากับ 2 mg Fe2+ equivalent/g rice powder สารสกัดข้าวที่ความเข้มข้น 25 mg/ml มีฤทธิ์ช่วยสมานแผลเมื่อทดสอบกับเซลล์ L929 ที่ได้รับบาดเจ็บ นำผงข้าวที่ผ่านการสกัดมาอบให้แห้งที่ 50 OC บรรจุลงในถุงชาขนาดเล็กแบบใช้ครั้งเดียว ของเหลวสำหรับกระจายผงข้าวเตรียมจากสารสกัดข้าว สารอีดีทีเอ กลีเซอรีน โพรพิลีนไกลคอล ไกลเด้น และพอลิไวนิลแอลกอฮอล์ เมื่อต้องการใช้ให้ผสมผงข้าว 1 ถุงกับของเหลวจนได้เพสเนื้อเนียน ทาเพสทั้งหมดลงบนของแข็งค้ำจุนผิวเรียบที่ทาน้ำมันไว้แล้ว เมื่อแห้งลอกฟิล์มที่เกิดขึ้นออกน้ำมันที่ทาลงไปตอนต้นจะถูกดึงออกระหว่างการลอกฟิล์มสามารถเพิ่มมูลค่าทางเศรษฐกิจของข้าวทับทิมสยามได้โดยผสมลงในเวชสำอาง คำสำคัญ: ข้าวทับทิมสยาม สารประกอบฟีนอลิกทั้งหมด ฤทธิ์ต้านออกซิเดชัน ฤทธิ์สมานแผล มาส์คพอกหน้าแบบลอกออก ABSTRACT Tub Tim Siam rice is an indigenous red rice variety of Thailand. The un-hulled rice was powdered and extracted by using ethanol. The obtained extract was investigated for phytochemicals by using GC-MS and HPLC techniques, total phenolic content (TPC) by using Folin-Ciocalteu reagent, antioxidant activity in regard to DPPH radical scavenging activity and ferric (Fe3+) reducing anti-oxidant power assays, and wound healing property according to the Scratch test. Phenolic compounds, anthocyanins, long chain fatty acids and fatty acid esters were presented in the extract. The TPC value was equal to 1.5 mg gallic acid/g of the rice powder. The DPPH radical scavenging activity and the Fe3+ reducing power were of 8 mg trolox equivalent and 2 mg Fe2+ equivalent/g, respectively. The extract exhibited wound healing property on injured L929 cells. After extraction, the rice residue was dried at 50OC and packed in single use pouches. Dispersing liquid that contains the extract, EDTA, glycerin, propylene glycol, glydant, and polyvinyl alcohol, was separately prepared and used for dispersing the rice residue in a pouch to obtain smooth paste. Transparent film was formed when left the paste to dry on solid support.Surfaced oil was effectively removed while the film was peeled off. Tub Tim Siam rice might be of economic value when incorporated in cosmeceutical products for improving skin appearance. Keywords: Tub Tim Siam rice, Total Phenolic Content, anti-oxidant activity, wound healing property, peeling face mask